Distinct impact of PI(4)P flux on PI(4,5)P 2 steady states and oscillations - X. J. Xǔ; C. S. Tong; M. Wu (Proceedings of the National Academy of Sciences, 2026)
Plasma membrane (PM) phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] regulates indispensable processes such as exocytosis, endocytosis, and actin cytoskeleton remodeling in eukaryotic cells. Since phosphatidylinositol 4-phosphate [PI(4)P] has long been regarded as the primary precursor of PI(4,5)P 2 , perturbing PM PI(4)P is expected to impact the dynamics of PM PI(4,5)P 2 . Yet, recent evidence suggests that PM PI(4)P has a limited role in the synthesis and function of PI(4,5)P 2 . In this paper, we address this puzzling discrepancy by studying the collective dynamics of PM PI(4)P and PI(4,5)P 2 . Leveraging live-cell imaging, we observed periodic traveling waves of PI(4)P on the PM of mast cells, challenging the notion that this precursor lipid is spatially homogeneous at the PM. We then found that a reduction in PM PI(4)P synthesis rate attenuated PI(4,5)P 2 oscillation amplitude while conserving the total PM density of PI(4,5)P 2 . We assessed the functional consequences of PI(4,5)P 2 oscillation amplitude by examining its interplay with Rho GTPase Cdc42, which cooperatively regulates the filamentous actin (F-actin) cytoskeleton with PI(4,5)P 2 . We showed that both PM PI(4)P and PI(4,5)P 2 oscillations are coupled to oscillations of membrane-bound active Cdc42. Finally, we demonstrated that lowering PM PI(4)P synthesis rate alone was sufficient to reversibly quench Cdc42 oscillations and to suppress F-actin oscillations. These results suggest that, beyond the steady-state regime, oscillations of PI(4,5)P 2 and its effector proteins require a critical threshold of PI(4)P flux.